Multiple Modes of College English Writing Feedback Enabled by Digital Intelligence Technology - Wu Tingting; Ma, Wenjia; Liu, Houtao; Zhao Xiaowen; Xin Chuanhua (Pacific International Journal, 2026)
With the rapid development of digital intelligence technology, the mode of college English writing feedback is undergoing profound transformation. Against the background of educational digital transformation, this paper systematically explores the multiple modes of college English writing feedback empowered by digital intelligence technology. The study finds that the multi-interactive feedback mode centered on AI preliminary assessment – peer assessment – teacher final assessment can effectively integrate technological advantages and humanistic care, forming a collaborative and orderly closed loop of teaching evaluation. The organic integration of the three can significantly improve students’ writing ability and learning motivation. This paper proposes that the transformation of a digital-intelligence-adaptive writing teaching paradigm should be promoted, the feedback mechanism should be optimized through human–computer collaboration, and a diversified feedback ecosystem integrating technological empowerment and humanistic care should be constructed.